Burden of colorectal cancer and its risk factors in the North Africa and Middle East (NAME) region, 1990-2019: a systematic analysis of the global burden of disease study - Fahimeh Haghighatdoost; Kamran Mehrabani-Zeinabad; Parisa Hajihashemi; Noushin Mohammadifard; Peyman Adibi (BMC, 2024)
Abstract Objective The geographical differences in incidence rates of colorectal cancer (CRC) and its burden due to modifiable risk factors warrant investigating the CRC burden and its risk factors in different regions. In the current study, we aimed to estimate the burden of CRC and the share of its risk factors in the North Africa and Middle East (NAME), from 1990 to 2019. Study design Systematic review. Methods The rates of incidence, prevalence, death, years of life lost (YLL), years lived with disability (YLD), and disability adjusted life years (DALYs) of CRC were estimated through the framework of the Global Burden of Diseases (GBD), Injuries and Risk Factors Study 2019 by age, sex, between 1990 and 2019. The CRC-related DALYs attributable to each lifestyle and metabolic risk factor was also estimated through a comparative risk assessment approach. Results In NAME region, the trends of incidence, prevalence, death, YLL, YLD, and DALYs of CRC were increasing, with higher rates in males than females over this period. High and high-middle socio-demographic index (SDI) countries had greater CRC DALYs rate compared with middle- and low-SDI countries in 2019, except for Palestine [434.66 (95% UI: 368.82, 503.88)]. In NAME region, like the global, dietary risk (33.18%), low whole grain intake (19.79%), and low intake of milk (15.77%) were the major contributing risk factors to DALYs due to CRC in 2019. Conclusions Due to increasing trend of CRC burden and the considerable role of lifestyle and metabolic factors in its burden in NAME region, implementing fundamental strategies to minimize CRC burden and its risk factors is imperative.